A comunidade de lianas da Estação Ecológica do Caiuá - PR : sua relação com a estrutura e composição florestal. - Pujals, Alexandrina (2014)
The aim of this study was to understand how the group of lianas influences the structure and composition of the tree community in a fragment of semideciduous forest. We sought to understand how this influence is reflected in certain environmental variables. In 25 parcels made in the Caiuá Ecological Station, located in Diamond North-PR, measures of individual trees in three categories perimeter were collected. We recorded the number of individuals of lianas in subplots whose data matrices made up of plenty and then dominance curves for each stratum of trees and lianas. To quantify the levels of agreement and determine which variables are most closely correlated with the distribution of vegetation, Procrustes analysis performed on the scores of a principal coordinates analysis (PCoA) applied to the matrices of abundance was used. Metrodorea nigra was the dominant specie in stratum 1 , 2 and 3 . The variable that had the highest correlation was moisture in the soil for the strata 1 and 3. The protest among strata and lianas gave mean for stratum 3. Thus, the community of lianas interfere with the tree community structure, showing the importance of including the plant group lianas to regeneration studies of plant community.